2009
DOI: 10.2337/db09-0016
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Liver Kupffer Cells Prevents the Development of Diet-Induced Hepatic Steatosis and Insulin Resistance

Abstract: OBJECTIVEIncreased activity of the innate immune system has been implicated in the pathogenesis of the dyslipidemia and insulin resistance associated with obesity and type 2 diabetes. In this study, we addressed the potential role of Kupffer cells (liver-specific macrophages, KCs) in these metabolic abnormalities.RESEARCH DESIGN AND METHODSRats were depleted of KCs by administration of gadolinium chloride, after which all animals were exposed to a 2-week high-fat or high-sucrose diet. Subsequently, the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
374
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(413 citation statements)
references
References 51 publications
18
374
3
3
Order By: Relevance
“…Interestingly, as earlier described for adipose tissue macrophages, alternative M2 activation phenotype of Kupffer cells appears to ameliorate insulin resistance and to delay the progression to NASH in mice [46]. These data suggest that steatosis might induce a sub-acute inflammatory response in liver, similar to that observed in the adipose tissue inflammation following adipocyte lipid accumulation.…”
Section: Page 8 Of 24supporting
confidence: 77%
See 2 more Smart Citations
“…Interestingly, as earlier described for adipose tissue macrophages, alternative M2 activation phenotype of Kupffer cells appears to ameliorate insulin resistance and to delay the progression to NASH in mice [46]. These data suggest that steatosis might induce a sub-acute inflammatory response in liver, similar to that observed in the adipose tissue inflammation following adipocyte lipid accumulation.…”
Section: Page 8 Of 24supporting
confidence: 77%
“…A c c e p t e d M a n u s c r i p t 8 production of inflammatory mediators that promote insulin resistance in liver [46]. Interestingly, as earlier described for adipose tissue macrophages, alternative M2 activation phenotype of Kupffer cells appears to ameliorate insulin resistance and to delay the progression to NASH in mice [46].…”
Section: Page 8 Of 24mentioning
confidence: 81%
See 1 more Smart Citation
“…We further observed that HFD exposure resulted in upregulated expression levels of TGF-b1 and collagen-a1 genes, as well as collagen synthesis, leading to slight hepatic fibrosis in the mice (Figures 2b and 5a-c, and Table 4). Other studies have showed that Kupffer cells (hepatic resident macrophages) are activated in diet-induced hepatic steatosis 42,43 and Kupffer cell-derived TGF-b1 initiates collagen production in hepatic stellate cells (HSCs). 44 It was also reported that lipid peroxidation in hepatocytes mediates the activation of HSCs in a rat model for hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in diabetic control animals the lobular architecture was maintained, but there was also vacuolation of the hepatocytes, fatty deposits, sinusoidal dilation and congestion, mild portal inflammation, severe degeneration and necrosis. The observed degeneration of the hepatocytes in untreated diabetic rats could be attributed to insulin deficiency and suppression of mitochondrial β-oxidation of fatty acids, leading to deposition of triglycerides in the hepatocytes (Huang et al 2010). However, diabetic rats treated with combined spice extract or glibenclamide showed hepatocytes with nearly normal appearance and minimal necrosis.…”
Section: Histopathological Evaluationmentioning
confidence: 99%